Training Program Influence in Enhancing Employee’s Performance at F&B Service the St. Regis Bali Resort - I Putu Bayu Andreawan; Ni Nyoman Triyuni; I Ketut Astawa (Jurnal Bisnis dan Kewirausahaan, 2022)
Training is an important thing carried out by companies that provide opportunities for employees to improve their skills related to work. The study, entitled "Enhancing Employee's Performance by Training Program at F&B Service the St. Regis Bali Resort” aims to find out how to improve the performance of F&B service employees through training programs at The St. Regis Bali Resort. Sample in this study amounted to 30 respondents. This study uses a sampling technique that is a saturated sample. Data collected using a questionnaire that has been tested for validity and reliability. The data analysis used is simple regression analysis technique. From the study result at a significant level of 5% show that the training program has a positive and huge impact on the performance of F&B service employees as proven by the beta coefficient (β) of 0.761. The training program can influence the performance of F&B service employees was (R2) 53.0%. Therefore, there will be an increment in the performance of F&B service employees by 0.761. With indicators of the training program, namely: type of training, training materials and time of implementation. Hotel management must maintain or develop training for increasing.